Penerapan Budaya 5S Terhadap Pembentukan Karakter Peserta Didik Kelas VI SD Negeri 1 Sinar Rejeki - Aprilya Saputri, Friska; Septiana; Dika Ramadhona, Zahra; Darsono (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2024)
The problem in this study is the low character formation of students through the implementation of the 5S culture (Smile, Polite, Courteous, Greet, and Greeting) in class VI of Elementary School 1 Sinar Rejeki. The purpose of this study was to determine the influence of the implementation of the 5S culture (Smile, Polite, Courteous, Greet, and Greeting) on the character formation of students in class VI of Elementary School 1 Sinar Rejeki. The research method used is a qualitative method using a descriptive approach involving direct intervention in the form of observation, implementation, supervision, and interviews on the implementation of the 5S culture (Smile, Polite, Courteous, Greet, and Greeting) in schools. The sample used in this study was 28 students in class VI with 11 male students and 17 female students. The results of the study indicate that the implementation of the 5S culture (Smile, Polite, Courteous, Greet, and Greeting) consistently can influence the positive behavior and character of students and can create a more harmonious learning environment in class VI of Elementary School 1 Sinar Rejeki.